2012
DOI: 10.2337/db11-1050
|View full text |Cite
|
Sign up to set email alerts
|

Brain Glucose Sensors Play a Significant Role in the Regulation of Pancreatic Glucose-Stimulated Insulin Secretion

Abstract: As patients decline from health to type 2 diabetes, glucose-stimulated insulin secretion (GSIS) typically becomes impaired. Although GSIS is driven predominantly by direct sensing of a rise in blood glucose by pancreatic β-cells, there is growing evidence that hypothalamic neurons control other aspects of peripheral glucose metabolism. Here we investigated the role of the brain in the modulation of GSIS. To examine the effects of increasing or decreasing hypothalamic glucose sensing on glucose tolerance and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 33 publications
6
47
1
Order By: Relevance
“…In support of our study, two recent reports (11,26) showed that hypothalamic glucose sensors play an important role in the control of insulin secretion (26) and that specific reduction of insulin receptor levels in the VMH produces glucose intolerance and islet dysfunction (11). Similar to this latter work, we found that Prep gt/gt mice have impaired glucose sensing and activation of insulin receptors in the VMH.…”
Section: Discussionsupporting
confidence: 80%
“…In support of our study, two recent reports (11,26) showed that hypothalamic glucose sensors play an important role in the control of insulin secretion (26) and that specific reduction of insulin receptor levels in the VMH produces glucose intolerance and islet dysfunction (11). Similar to this latter work, we found that Prep gt/gt mice have impaired glucose sensing and activation of insulin receptors in the VMH.…”
Section: Discussionsupporting
confidence: 80%
“…In light of CEACAM2 expression in the ventromedial hypothalamus (1), the glucose-sensing center in (30), it is possible that hypothalamic CEACAM2 regulates insulin secretion centrally (31,32) and independently of GLP-1 release (33). Disturbance in this neuronally mediated mechanism may contribute to the higher excursion of insulin during hyperglycemic clamp analysis in Cc2 Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, many amino acids including tyrosine, tryptophan, proline, histidine, glycine, phenylalanine, cysteine, and arginine interfere non-significantly with glucose determination. Experimental results also show that ions SO 4 2-, acetate (Ac -), NO 3 -, ClO 4 -, PO 4 3-, Cl -, NH 4 ? , NO 2 -, and F -have negligible interference with determination of glucose.…”
Section: Selectivity Of B(oh) 3 -Tga@cdte Qds' Sensormentioning
confidence: 78%
“…related to many diseases including diabetes, cancers, and physiological aging and neurodegenerative diseases [4][5][6]. Therefore, a large number of methods have been developed to detect glucose using organic probes functionalized with borates/boronic acids [7], such as phenylboronic acid [8], anthrylboronic acid [9], ferrocenylboronic acids [10], cyanine dye possessing boronic acid [11], boronic acid gel [12], boronic acid functionalized benzyl viologen derivative, and/or boronate-functionalized polymeric monoliths over past few decades [2,13].…”
Section: Introductionmentioning
confidence: 99%